2002
DOI: 10.1097/00000542-200204000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Infusion Pumps during Hyperbaric Conditions

Abstract: Commercially available infusion pumps operating during hyperbaric conditions demonstrate substantial variations in performance and accuracy. It is therefore important that the hyperbaric facility staff make a careful examination of such instruments to anticipate possible deviations in the accuracy of the equipment during use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Dysfunction of devices used to deliver these drugs during hyperbaric oxygen therapy may compromise their safety. Studies, case reports and letters have demonstrated the problems associated with specific infusion devices [4][5][6][7][8][9][10][11][12], which we have replicated in our institution (unpublished results). Some devices fail completely at normal treatment pressures [6,7,11], whereas others deliver inconsistent flow rates.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Dysfunction of devices used to deliver these drugs during hyperbaric oxygen therapy may compromise their safety. Studies, case reports and letters have demonstrated the problems associated with specific infusion devices [4][5][6][7][8][9][10][11][12], which we have replicated in our institution (unpublished results). Some devices fail completely at normal treatment pressures [6,7,11], whereas others deliver inconsistent flow rates.…”
supporting
confidence: 64%
“…Studies, case reports and letters have demonstrated the problems associated with specific infusion devices [4][5][6][7][8][9][10][11][12], which we have replicated in our institution (unpublished results). Some devices fail completely at normal treatment pressures [6,7,11], whereas others deliver inconsistent flow rates. Infusion devices of different types have been examined in hyperbaric environments, including syringe drivers [5,7,8,11], volumetric devices [4,6,9,11,12], peristaltic pumps [11,13], and vacuum-powered [10], spring powered [10] and balloon-type [10] devices.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Most infusion pumps are unacceptable for use under hyperbaric conditions. 24 Safe HBOT for a critically-ill infant requires sufficient specially trained personnel; here this comprised an adult intensive care nurse, a pediatric respiratory therapist and a hyperbaric physician inside and a hyperbaric physician, adult critical care nurse, pediatric intensive care nurse, pediatric intensivist and technical staff (supervisor and chamber operator) outside the chamber.…”
Section: éLéments Cliniques : Un Bébé De Quatre Mois De Sexe Masculimentioning
confidence: 99%
“…It may be possible to use infusion pumps under hyperbaric conditions in patients with anaerobic infection, 7 arteriosclerotic obliteration, or a critical condition such as carbon monoxide poisoning. 8 There is a report on the performance of infusion pumps under hyperbaric conditions, 8 and it is concluded that commercially available infusion pumps operating under hyperbaric conditions demonstrated substantial variations in performance and accuracy. We are exposed to changes in atmospheric pressure in daily life.…”
mentioning
confidence: 99%